Bonelike/PLGA hybrid materials for bone regeneration: in vivo evaluation - Oliveira, Joaquim M. (2004)
The biocompatibility and osteoconductive potential of Bonelike and Bonelike /PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike /PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike resorption was recognized, which may be due to the presence of resorbable and -tricalcium phosphate phases.